2015
DOI: 10.1002/2015gl064955
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Earth injection of MeV electrons associated with intense dipolarization electric fields: Van Allen Probes observations

Abstract: Substorms generally inject tens to hundreds of keV electrons, but intense substorm electric fields have been shown to inject MeV electrons as well. An intriguing question is whether such MeVelectron injections can populate the outer radiation belt. Here we present observations of a substorm injection of MeV electrons into the inner magnetosphere. In the premidnight sector at L ∼ 5.5, Van Allen Probes (Radiation Belt Storm Probes)‐A observed a large dipolarization electric field (50 mV/m)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 59 publications
3
77
0
Order By: Relevance
“…Therefore, it would be reasonable to suggest that the energy gain process of the high‐energy (>50 keV) electron population inside GEO is primarily achieved by an efficient betatron acceleration in the course of the dipolarization. A similar conclusion was reached by Dai et al (), who examined a case of dipolarization‐related MeV electron injections inside GEO.…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, it would be reasonable to suggest that the energy gain process of the high‐energy (>50 keV) electron population inside GEO is primarily achieved by an efficient betatron acceleration in the course of the dipolarization. A similar conclusion was reached by Dai et al (), who examined a case of dipolarization‐related MeV electron injections inside GEO.…”
Section: Discussionsupporting
confidence: 80%
“…In the course of the dipolarizing magnetic field, a strong westward electric field (a few mV/m up to several tens of mV/m) is often observed in the inner magnetosphere (Aggson et al, ; Dai et al, ; Ohtani et al, ). Such electric fields, which are likely inductive, are possibly responsible for local nonadiabatic acceleration, which leads to the mass‐dependent injection signature (Delcourt, ).…”
Section: Introductionmentioning
confidence: 99%
“…While radial diffusion caused by ULF waves can redistribute relativistic electrons and change the energy of MeV electrons, which depends on the radial gradient of the electron PSDs [e.g., Elkington et al, 1999;Hudson et al, 1999;Ukhorskiy et al, 2009;Huang et al, 2010;Su et al, 2015]. Recently, some studies have also shown that enhanced convection and substorm electron injections can directly explain the rapid enhancement of the outer radiation belt [e.g., Kress et al, 2014;Dai et al, 2014Dai et al, , 2015Su et al, 2014c;Tang et al, 2016b].…”
Section: Introductionmentioning
confidence: 99%